O-024 Cost comparison of endovascular treatment of anterior circulation aneurysms with the pipeline embolization device vs stent-assisted coiling. (4th July 2012) - Colby, G; Lin, L; Paul, A; Huang, J; Tamargo, R; Coon, A
Abstract : Introduction: The Pipeline embolization device (PED) is an efficacious endovascular option for anterior circulation aneurysms with broad-based, fusiform involvement of the parent vessel. Endovascular treatment of such aneurysms has classically involved coil embolization with adjunctive use of a stent. However, stent-coiling can incur significant equipment and implant costs, particularly if the aneurysm is large and numerous coils are used. The authors hypothesized that PED embolization is a cost effective alternative to stent-assisted coiling. Methods: A prospective single-center aneurysm database was retrospectively reviewed to identify consecutive patients with anterior circulation aneurysms who underwent aneurysm treatment with the PED or by single-staged stent-assisted coiling. Thirty consecutive patients were selected in each group, for a total of 60 patients. The hospital cost of equipment and implants were analyzed and compared for each group. Results: Hospital equipment and implant costs were analyzed for 30 consecutive aneurysm treatments with the PED (mean aneurysm size 9.8 mm) vs 30 consecutive cases of stent-assisted coiling (mean aneurysm size 7.3 mm). The total combined cost of proximal access/guide catheters, microcatheters, and microwires were equivalent between the two groups (PED 3057±102 vs stent-coiling 3199±126, p=0.3927). The cost of implants, however, was significantly lower in the PED group (13 175±726 vs 19 069±2015, p=0.0126), despite this group having a larger mean aneurysm size. Furthermore, the total cost (equipment, implants, and adjunctive devices) was significantly lower for the PED group vs the stent-coiling group (16 445±735 vs 22 145±2022, p=0.0181), representing a 25.7% cost reduction. This represents a 27.1% reduction in the cost per millimeter of aneurysm treated in the PED group (2261±299) vs the stent-coiling group (3102±193, p=0.0202). Conclusion: Treatment of anterior circulation aneurysms by flow diversion with the PED is a cost effective alternative to traditional stent-assisted coiling. Competing interests: G Colby: None. L Lin: None. A Paul: None. J Huang: None. R Tamargo: None. A Coon: Covidien.